2022
DOI: 10.3390/ijms232315399
|View full text |Cite
|
Sign up to set email alerts
|

Light Emission from M-Type Enantiomer of 2,13-bis(hydroxymethyl)[7]-thiaheterohelicene Molecules Adsorbed on Au(111) and C60/Au(111) Surfaces Investigated by STM-LE

Abstract: Light emission from the M-type enantiomer of a helicene derivative (2,13-bis(hydroxymethyl)[7]-thiaheterohelicene) adsorbed on the clean Au(111) and the C60-covered Au(111) surfaces were investigated by tunneling-current-induced light-emission technique. Plasmon-originated light emission was observed on the helicence/Au(111) surface and it was strongly suppressed on the area where the helicene molecules were adsorbed at the edges of the Au(111) terraces. To avoid luminescence quenching of excited helicene mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Heterohelicenes, which are composed of several different types of aromatic ring, have also been intensively investigated. [16][17][18][19][22][23][24][25][26] For example, 7,12,17-trioxa [11]helicene, which consists of benzene and furan rings, forms homochiral square clusters on Cu(100) 22 and Ag(100) substrates 23 at a low coverage. It is suggested that the interaction between the substrate and the molecule affects the chiral recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Heterohelicenes, which are composed of several different types of aromatic ring, have also been intensively investigated. [16][17][18][19][22][23][24][25][26] For example, 7,12,17-trioxa [11]helicene, which consists of benzene and furan rings, forms homochiral square clusters on Cu(100) 22 and Ag(100) substrates 23 at a low coverage. It is suggested that the interaction between the substrate and the molecule affects the chiral recognition.…”
Section: Introductionmentioning
confidence: 99%